“Nobody has the answer, but we need some map, even to go into the unknown”: A Conversation with Arjun Appadurai on Research, Speculation and Future Thinking - de Aquino, Elis; Kliche, Luis (Critical Reviews on Latin American Research - CROLAR, 2021)
Arjun Appadurai is a cultural- anthropologist born in Mumbai (1949) and based between New York, where he is Paulette Goddard Professor in Media, Culture, and Communication at New York University, and Berlin, where he is currently Mercator Fellow at the International Research Training Group Temporalities of Future in Latin America at the Freie Universität Berlin, funded by the German Research Foundation DFG. In this conversation, PhD candidates at the IRTG Elis de Aquino and Luis Kliche address some of the different and diverse themes that occupy Appadurai’s career, from digital capitalism to education, as well as Appadurai’s experience with Latin American researchers and institutions, in an exercise to imagine the possible future horizons at the global and local level. This interview was carried out online in December 2020.